THE GIG ECONOMY AND ITS IMPACTS ON INDIAN BUSINESS AND LABOR MARKETS - Singh, Dhananjay Kumar; Singh, Binod Pratap (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The gig economy has revolutionized business practices and labor markets around the world and is one of the fastest-growing markets in India. Composed of short-term, flexible, and platform-driven job relations, the gig economy opens up enormous potential for commercial extension but also poses fundamental questions about labor rights and social security. The above points are confirmed by our analysis of secondary data from government reports, policy papers, and academic research, with a specific focus on what trends in the “gig economy” entail for Indian commerce and labor markets. It is clear from the analysis that gig platforms (e.g., Ola, Uber, Swiggy, Zomato, and freelance IT services) have disrupted legacy commercial models, driving down operational expenses for organizations and starting consumer-centric modes of service provisioning. Nevertheless, the research also finds that gig workers suffer from precarious incomes, overwork, and absence of social protection. Using case studies, I show how gig platforms enable work while reproducing structural vulnerabilities of the Indian informal economy. The paper contends that the gig economy adds efficiency and growth in Indian commerce, but at the same time, it also aggravates the precarious nature of the labor market situation. A balanced policy regime is necessary to ensure that innovation-driven commerce is in accordance with fair labor standards.